KHILAFAH RASYIDAH: KAJIAN ATAS MAKNA, FUNGSI DAN SISTEM SUKSESINYA - Yusuf, Burhanuddin (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2015)
This article examines the concept of khulafah Rasyidin historically by digging meanings, functions and system of succession. The method used in this study is a qualitative method. The author describes the events that occurred during the Rasyidin khulafa associated with the main task of the caliphate and the trajectory of political events that occurred during the turn of the caliphate succession. A variety of events that characterize the succession of governments khulafa Rashidun then analyzed, examined and compared leadership typology of each caliph Rasyidin. Khalifah himself is a title given to those who got the mandate to take the place of the Prophet Muhammad. As a real leader on the world and the Muslims with two main functions, namely as a Muslim leader who must operate a system of governance and as a guard at the same carrier religious treatise, namely Islam. Governmental system of Khilafat al-Rasyidin commonly used as a form of Islamic rule best, it does not have a permanent form, because each caliph who ruled implement its own system, the rhythm of the circumstances that occurred in his time people each.